Assessment of the effect of different imaging techniques on planning implant therapy by different clinicians (Annals of Medical Research, 2021)
Aim: To compare the implant size which was determined by different observers using panoramic radiography (PAN) and cone beam computed tomography (CBCT) with inserted implant size.Material and Methods: 194 PAN and CBCT images which belong to 194 patients who were planned to undergone single-tooth implant therapy were evaluated. 50 anterior regions, 42 premolar regions and 92 molar regions were assessed. These sites were used for planning of dental implant insertion. Images were analyzed by observers with different education and clinic experience backgrounds: one periodontist (observer 1), one oral and maxillofacial radiologist (observer 2), and one general practitioner (observer 3). Panoramic images and cross-sectional CBCT images of each patient were examined; differences in length and width of the implant-to-be from the two imaging systems were analyzed and compared to inserted implant size.Results: Observer 2 recorded the largest implant width whereas observer 3 recorded narrower implants in PAN. Observer 3 recorded shortest implants than did the other two observers in CBCT and observer 2 recorded narrower implants in CBCT. The CBCT measurements allowed a wider implant in the premolar and molar regions. No significant difference was observed between CBCT and PAN in planning the implant length. The inserted implant size was smaller than the measurements made in CBCT.Conclusion: The results show that; different observers present different values in determining implant length and width. The inserted implant size and the dimensions measured on CBCT and PAN images were different.